2005
DOI: 10.1089/ars.2005.7.1630
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitization and Radiosensitization of Tumors by Plant Polyphenols

Abstract: The treatment of cancer with chemotherapeutic agents and radiation has two major problems: time-dependent development of tumor resistance to therapy (chemoresistance and radioresistance) and nonspecific toxicity toward normal cells. Many plant-derived polyphenols have been studied intently for their potential chemopreventive properties and are pharmacologically safe. These compounds include genistein, curcumin, resveratrol, silymarin, caffeic acid phenethyl ester, flavopiridol, emodin, green tea polyphenols, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
156
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(160 citation statements)
references
References 169 publications
2
156
1
1
Order By: Relevance
“…Among these, curcumin (2,3), and many other polyphenol derivatives (31,32,33,46,49,52,53,54) have been found to inhibit NF-B pathway in several tumor cell lines and at different levels, from I B phosphorylation to the expression of NF-B-regulated gene products. These novel findings could be of great importance in cancer prevention and therapy (27), especially in light of the latest evidence that demonstrates a pivotal role for NAD(P)H:quinone oxidoreductase 1 (NQO1) in producing ROS downstream of TNF engagement, in keratinocytes from NQO1 -/-mice (4). The genetic deletion of NQO1 used in this study abrogates the phosphorylative cascade mediated by MEKK1, which concomitantly activates I B kinase (IKK)/ NF-B signaling axis and all the members of the MAP kinase family: JNK, p38 MAPK , and p42/44 extracellular signalregulated kinase 1/2 (ERK1/2) (4).…”
Section: Redox-regulated Response To Cell Surface Receptors Engagementmentioning
confidence: 99%
“…Among these, curcumin (2,3), and many other polyphenol derivatives (31,32,33,46,49,52,53,54) have been found to inhibit NF-B pathway in several tumor cell lines and at different levels, from I B phosphorylation to the expression of NF-B-regulated gene products. These novel findings could be of great importance in cancer prevention and therapy (27), especially in light of the latest evidence that demonstrates a pivotal role for NAD(P)H:quinone oxidoreductase 1 (NQO1) in producing ROS downstream of TNF engagement, in keratinocytes from NQO1 -/-mice (4). The genetic deletion of NQO1 used in this study abrogates the phosphorylative cascade mediated by MEKK1, which concomitantly activates I B kinase (IKK)/ NF-B signaling axis and all the members of the MAP kinase family: JNK, p38 MAPK , and p42/44 extracellular signalregulated kinase 1/2 (ERK1/2) (4).…”
Section: Redox-regulated Response To Cell Surface Receptors Engagementmentioning
confidence: 99%
“…Radiotherapy is the major therapeutic technique to minimize the effect of cervical cancer but due to its adverse effect on normal tissues, alternative plant-derived therapeutic drugs are being tested increasingly (Seiwert et al 2007). A large number of natural compounds have shown cytotoxic effects in different cancer models either alone or together with radiation (Garg et al 2005). Effects of FA on human cervical carcinoma cells ME-180 and HeLa have been studied and indicated that FA treatment significantly decreased radiation surviving fraction of the cancer cells and increased the lipid peroxidation indices (Subburayan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among nutraceuticals, polyphenols represent the most intriguing and studied class of compounds that can be therapeutics for a large spectrum of the most common diseases including cancer [20]. Nevertheless, despite several studies regarding their function, the anti-oxidant/prooxidant properties of these compounds remain somewhat debatable and the detailed molecular mechanisms of their effects continue to be largely unknown.…”
Section: Introductionmentioning
confidence: 99%